Relevance of KH. Hasyim Asy’ari’s Thought on Character Education in The Era of Society 5.0 - Arifin, Bustanul; Baihaqi, Moh. Hamdan (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
The rapid advancement of technology and moral challenges in modern society create an urgent need for robust character education, making the thoughts of KH. Hasyim Asy’ari on character education highly relevant for examination. This study aims to analyze how the principles of character education proposed by KH. Hasyim Asy’ari can be applied in the context of Society 5.0, where the integration of moral values and technological sophistication is of primary importance. The research method employed is library research, utilizing Miles and Huberman’s data analysis techniques. The results indicate that values such as sincerity, humility, and discipline in character education remain relevant and can guide the development of individuals with noble character in the digital era. The contribution of this research is to provide valuable insights into the synergy between Islamic values and the need for character education in shaping a generation that is ready to face future challenges.